Plasma ET-1 Concentrations Are Elevated in Pregnant Women with Hypertension -Meta-Analysis of Clinical Studies - Yong-Ping Lu; Ahmed Abdallah Hasan; Shufei Zeng; Berthold Hocher (Karger Publishers, 2017)
Background/Aims: The ET system might be involved in the pathogenesis of hypertensive disorders during pregnancy. The objective is to analyse the impact of ET-1 in hypertensive pregnant women by a strict meta-analysis of published human clinical studies. Methods: Based on the principle of Cochrane systematic reviews, Cohort studies in PubMed (Medline), Google Scholar and China Biological Medicine Database (CBM-disc) designed to identify the role of endothelin-1 (ET-1) in the pathophysiology of gestational hypertension and preeclampsia were screened. Review Manager Version 5.0 (Rev-Man 5.0) was applied for statistical analysis. Mean difference and 95% confidence interval (CI) were shown in inverse variance (IV) fixed-effects model or IV random-effects model. Results: Sixteen published cohort studies including 1739 hypertensive cases and 409 controls were used in the meta-analysis. ET-1 plasma concentrations were higher in hypertensive pregnant women as compared to the controls (mean difference between groups: 19.02 [15.60～22.44], P < 0.00001,). These finding were driven by severity of hypertension and/or degree of proteinuria. Conclusion: Plasma ET-1 concentrations are elevated in hypertensive disorders during human pregnancy. In particular women with preeclampsia (hypertensive pregnant women with proteinuria) have substantially elevated plasma ET-1 concentration as compared to pregnant women with normal blood pressure.